Exploring Folk Art - Jones, Michael O. (Utah State University, University Libraries, 1987)
Jones explores the human impulse to create, the necessity for having aesthetically satisfying experiences, and the craving for tradition. He also considers topics such as making chairs, remodeling houses, using and preserving soda-fountain slang, preparing and eating food, and sculpting lifelike figures out of cement.